Lipomyelomeningocele: Epidemiological Studies in a Pediatric Neurosurgery Department of Bangladesh (Bangladesh Journal of Neurosurgery, 2022)
Background: Spinal dysraphism, one of the most common birth defects, has been estimated to occur annually in more than 320,000 infants worldwide. Lipomyelomeningocele (LipoMMC) is a closed neural tube defect in which the surface lipomatous tissue is attached to the spinal cord. LipoMMC results from premature disjunction of the epithelial ectoderm from the neural ectoderm at a gestational age of 18–28 postovulatory days.Both genetic and environmental factors are suggested to have important roles in the occurrence of neural tube defects. In addition, variables such as vitamin B 12 deficiency, maternal hyperinsulinemia,maternal dietary glycemic intake, maternal obesity and use of antiepileptic medications during pregnancy have been suggested as risk factors for spinal dysraphism.Objective:The aims and objectives of this study was to see the epidemiology of Lipomyelomeningocelein our population. We shall also compare our result with other previous study result.Materials and method: It is a retrospective study. Cases were obtained from a NINS Pediatrics neurosurgery electronic registry (emrbd.com). The study was carried out at Department of Paediatrics Neurosurgery, NINS&H, and DhakafromNovember 2017 to till date.Subjects was included from a NINS Pediatrics neurosurgery electronic registry.Structured questionnaire was used to collect the necessary information. Risks and benefits of this study were explained to the patient and patient’s legal guardian/ parents in an easily understandable local language.Conclusion: In this study the majority of cases were female. Environmental factors also appear to be associated with lipomyelomeningocele risk factor. Additional studies needed to establish the environmental risk factor associated with LipoMMC.Bang. J Neurosurgery 2021; 11(1): 25-29